Effectiveness of Mediation in Preventing Divorce in the Sungguminasa Class I B Religious Court in 2022 - Jumik, Jumik; Muchtar, M Ilham; Abidin, Zainal (Family Law Study Program (Ahwal Syakhshiyah), Universitas Muhammadiyah Makassar, 2023)
This study discusses the issue of the Effectiveness of Mediation in Divorce Prevention at the Sungguminasa Religious Court in 2022. Mediation is a way of resolving disputes through the negotiation process to obtain agreement between the parties assisted by a mediator. This is motivated by the high number of divorce cases entered at the Sungguminasa Religious Court in 2022. So the author conducted a study with the aim of knowing how effective mediation is in preventing divorce at the Sungguminasa Religious Court in 2022 and what factors are supporting and inhibiting the success of mediation in preventing divorce at the Sungguminasa Religious Court in 2022. The author uses qualitative methods, the data sources used are primary data and secondary data. Then data collection using observation, interview, and documentation methods. The results of this study show that the legal basis used by the Courts, especially Religious Courts, is Law No. 1 of 1974, PERMA No. 1 of 2008, PERMA No. 1 of 2016. In the implementation of mediation, not a few have failed and not a few have succeeded due to various things, the results of mediation at the Sungguminasa Religious Court in 2022 were declared quite effective.